2019
DOI: 10.1080/13102818.2019.1621208
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of probiotic dietary supplements

Abstract: Today people focus on healthy lifestyle. It is well known that probiotics have a number of beneficial health effects in humans. They play an important role in protecting the host against harmful microorganisms, reduce metabolic disorders and support immune functions. In the present study, we investigated 26 probiotic products: 16 commercially available ones and 10 from a local manufacturer. None of the commercial products contained all labelled LAB and some of them contained unacceptable microorganisms. Of 890… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…All the Polish probiotic formulations included in the study by Szajewska et al (2004) complied with the label claims for content of viable cells. The analysis of the content of living microbes in 26 supplements sold in Bulgaria revealed that for 10 there was concordance with the label claims (Yonkova Marinova et al, 2019).…”
Section: Amount Of Viable Cellsmentioning
confidence: 63%
See 4 more Smart Citations
“…All the Polish probiotic formulations included in the study by Szajewska et al (2004) complied with the label claims for content of viable cells. The analysis of the content of living microbes in 26 supplements sold in Bulgaria revealed that for 10 there was concordance with the label claims (Yonkova Marinova et al, 2019).…”
Section: Amount Of Viable Cellsmentioning
confidence: 63%
“…In this study, we also evidenced that the labels of some formulations, particularly functional foods, did not comply general guidelines for probiotic labeling, since not indicating the contained microbes or only reporting a general and inaccurate description (e.g., "LAB, " "probiotics, " "lactic ferment, " "lactic acid bacillus, " "live probiotic AB cultures, " "active bifidus, " "special live cultures, " "viable LAB, " "bifidus essensis, " "life yeast") (Fasoli et al, 2003;Temmerman et al, 2003a,b;Elliot and Teversham, 2004;Masco et al, 2005;Theunissen et al, 2005;Lin et al, 2006;Perea Vélez et al, 2007;Angelakis et al, 2011;Chen et al, 2014;Kesavelu et al, 2020). In addition, we found that some preparations only indicated the contained microbes at the genus level, thus resulting in disagreement with the FAO/WHO guidelines (Fasoli et al, 2003;Temmerman et al, 2003a,b;Masco et al, 2005;Theunissen et al, 2005;Lin et al, 2006;Perea Vélez et al, 2007;Chen et al, 2014;Yonkova Marinova et al, 2019).…”
Section: Microbial Compositionmentioning
confidence: 81%
See 3 more Smart Citations